The Relationship Between Sleep Patterns and Blood Pressure in 7th Semester Students of the Faculty of Nursing, Adventist University of Indonesia - Hutajulu, Raja; Boyoh, Debilly Yuan (Jurnal Biologi Tropis, 2025)
A person's ability to wake up feeling refreshed and fit is influenced by the quality of their sleep. If a person does not have symptoms of sleep deprivation and does not experience difficulty sleeping, then their sleep needs are said to be met. The purpose of this study was to determine the relationship between sleep patterns and blood pressure in seventh-semester students of the Faculty of Nursing, Adventist University of Indonesia. The research method used a quantitative approach with a descriptive correlative design and sampling using total sampling. Data were analyzed using univariate and bivariate analysis through the Spearman R correlation test. The results of the study showed that only 11 respondents (23.9%) had good sleep habits, while the majority of respondents (35, or 76.1%) had poor sleep patterns. Most respondents (45 people) had normal blood pressure, and only 1 person (2.2%) had hypertension. These results indicate that in general, students' blood pressure is still within normal limits, although risk factors such as stress and unhealthy lifestyles still need to be considered. The correlation coefficient of -0.084 and p-value of 0.581 (p>0.05) were determined by statistical tests using the Spearman's rho correlation test. The conclusion was that there was no significant correlation between the students' blood pressure and their sleep habits. Although the negative direction of the relationship suggests a tendency for poorer sleep patterns to lead to a slight increase in blood pressure, this relationship was very weak and not statistically significant.